Transmedia discourse in the digital age: Exploring radical intertextuality, audiovisual hybridization, and the “aporia” of homo medialis - Pecheranskyi, Igor; Humeniuk, Tetiana; Shvets, Nataliia; Holovkova, Marianna; Sibiriakova, Olena (Research Journal in Advanced Humanities, 2023)
This article explores the evolution of transmedia discourse, a trend that emerges from the interplay between technological advancements and the modern individual's worldview, and its impact on contemporary media practices. The study focuses on the principles of radical intertextuality in convergent and television journalism, demonstrating how these principles contribute to the development of performativity, extraction, media symbiosis, and hybridization processes in screen arts. Additionally, the article delves into multimodal storytelling techniques, shedding light on the increasing demand for non-linear narratives and aesthetic models. The analysis concludes with an examination of the "aporia" of homo medialis within the context of digital anthropology, emphasizing the need for a better understanding of the human experience and identity in an increasingly interconnected digital landscape. The results of this investigation provide valuable insights for media scholars, industry professionals, and educators, with a focus on adapting to and leveraging the ever-shifting media landscape.